Meta-Analysis: Factors Reducing Health Workers' Willingness to Leave Work - Hidayat, Fany Nurul Fawzi; Raharjo, Setyo Sri; Ichsan, Burhannudin (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Employees are the most important human resource in a company because they have a direct influence on institutional operations in achieving organizational goals. The main problem in health service management is a shortage of health workers due to turnover or intention to leave work. This research aims to analyze the factors that reduce the desire to leave among health personnel. Subjects and Method: This research uses a meta-analysis based on PICO as follows; population: health workers; intervention: satisfied autonomy, good working environment, length of service > 5 years, low workload; comparison: autonomy not satisfied, poor working environment, length of service < 5 years, high workload; outcome: intention to leave work. Data was obtained from the PubMed, Google Scholar, Science Direct databases published from 2013-2022. The keywords in the article search are